Kajian Perlindungan Implementasi Hak Asasi Manusia Bagi Narapidana Perempuan - fiqih bagus aryo seno (Widya Yuridika, 2020)
Female correctional Institution must implement the female convict rights in accordance with the legislation – the invitation. Implementation of female convict protection can be seen from various aspects of rights already accepted by prisoners and that have been applied by the correctional institution, of course with the support of good facilities and infrastructure. The study at the women's Prison of IIA Jakarata Timur using a historical approach resulted in the implementation of a female convict human rights protection has not run optimally. There are 5 aspects of the 12 aspect criteria that need to get special attention.Keywords: , ,